Reproductive tactics optimizing the survival of the offspring of Cichlasoma orientale (Perciformes: Cichlidae) - Spíndola Linhares, Jussiara Candeira; Resende Manna, Luisa; Mazzoni, Rosana; Ferreira Rezende, Carla; Feitosa Silva, José Roberto (Revista de Biología Tropical, 2014)
High mortality rates have been observed in Teleost during early developmental stages, as well as great variations in reproductive tactics, which are related to adaptations towards environmental conditions and ecological niches for which different species have a specific response. The objective of this study was to describe reproductive tactics related to the survival of Cichlasoma orientale offspring, including aspects of body size, parental care, fecundity, oocyte size and spawning patterns. Samples were performed monthly from August 2011 to July 2013, in lentic and lotic environments at Curu river basin, Brazilian Northeastern semiarid region. Individual behavior (n=113) was observed underwater for over 50 hours by ad libitum sampling and focal-animal sampling. Collected individuals (males n=185, females n=95) were evaluated regarding the standard length, batch fecundity, oocyte size and spawning pattern. In females with mature ovaries, oocyte groups at different developmental stages were observed, these cells were counted and measured, and fecundity was estimated by the gravimetric method. Our results showed that the species displayed biparental care behavior and, on average, males were larger than females. Based on 46 ovaries, the average batch fecundity was 2 052±849 (range: 254-3 389). Standard length and batch fecundity were positively correlated, but no correlation was found between oocyte size and standard length. The maximum diameter observed in the most developed oocytes was 1.8mm. The observed distribution of oocyte size classes indicated synchronous oocyte development in three groups: previtellogenic, vitellogenic and mature, showing that C. orientale is a multiple spawner. Differences in the amount of oocytes among the three groups were observed, with the most developed group showing the smallest number of oocytes. The combination of low fecundity and large egg size is characteristic of demersal spawners due to a greater environmental stability. Multiple spawning increases chances of survival mainly because of increased fecundity per reproductive season, and the reduced competition among the offspring. We concluded that C. orientale makes a heavy investment in larval survival in detriment of the offspring number. Survival is favored by the large size of oocytes, large yolk reserve, biparental care and multiple spawning pattern.